Protein and Sport: Alternative Sources and Strategies for Bioactive and Sustainable Sports Nutrition - López-Martínez, Manuel I.; Miguel, Marta; Garcés-Rimón, Marta (Frontiers in Nutrition, 2022)
Nutrition and sport play an important role in achieving a healthy lifestyle. In addition to the intake of nutrients derived from the normal diet, some sport disciplines require the consumption of supplements that contribute positively to improved athletic perfor-mance. Protein intake is important for many aspects related to health, and current evi-dence suggests that some athletes require increased amounts of this nutrient. On the oth-er hand, society's demand for more environmentally friendly products, focus on the search for alternative food sources more sustainable. This review aims to summarize the latest research on novel strategies and sources for greener and functional supplementa-tion in sport nutrition. Alternative protein sources such as insects, plants or mycopro-teins have proven to be an interesting substrate due to their high added value in terms of bioactivity and sustainability. Protein hydrolysis has proven to be a very useful tech-nology to revalue by-products, such as collagen, by producing bioactive peptides bene-ficial on athletes performance and sport-related complications. In addition, it has been observed that certain amino acids from plant sources, as citrulline or theanine, can have an ergogenic effect for this target population. Finally, the future perspectives of protein supplementation in sports nutrition are discussed. In summary, protein supplementation in sports nutrition is a very promising field of research, whose future perspective lies with the search for alternatives with greater bioactive potential and more sustainable than conventional sources.